Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(62007-62006):62006=\(\frac{6^{2007}-6^{2006}}{6^{2006}}\)=62007
Các bài con lại làm tương tự!!!
\(\left(6^{2007}-6^{2006}\right):6^{2006}\)
\(=6^{2007}:6^{2006}-6^{2006}:6^{2006}\)
\(=6^{2007-2006}-1\)
\(=6^1-1\)
\(=6-1\)
\(=5\)
\(\left(7^3+7^5\right).\left(5^4+5^6\right).\left(3^3.3-9^2\right)\)
\(=\left(7^3+7^5\right).\left(5^4+5^6\right).\left(3^{3+1}-9^2\right)\)
\(=\left(7^3+7^5\right).\left(5^4+5^6\right).\left(3^4.9^2\right)\)
\(=\left(7^3+7^5\right).\left(5^4+5^6\right).\left[3^4-\left(3^2\right)^2\right]\)
\(=\left(7^3+7^5\right).\left(5^4+5^6\right).\left(3^4-3^4\right)\)
\(=\left(7^3+7^5\right).\left(5^4+5^6\right).0\)
\(=0\)
a. 84 : 4 + 39 : 37 + 50
= 21 + 32 + 1
= 21 + 9 + 1
= 21 + 10 = 31
b. 2010 - 2000 : [ 486 - 2.(72 - 6) ]
= 2010 - 2000 : [ 486 - 2.(49 - 6) ]
= 2010 - 2000 : ( 486 - 2.43 )
= 2010 - 2000 : ( 486 - 86 )
= 2010 - 2000 : 400
= 2010 - 5
= 2005
c. 62 - 120 + (-5) - |-5|
= 36 - 120 - 5 - 5
= 36 -
( 62007 - 62006 ) : 62006
= 62007 : 62006 - 62006 : 62006
= 6 - 1
= 5.
\(a)\dfrac{5^{2001}-5^{2000}}{5^{2000}}=\dfrac{5^{2001}}{5^{2000}}-1=5-1=4\)
\(b)\dfrac{6^{2007}-6^{2006}}{6^{2006}}=\dfrac{6^{2007}}{6^{2006}}-1=6-1=5\)